Learning Media Implementation Training At SDN No.101763 Klumpang Kampung - Linda Wahyuni; Hardianto Hardianto; Rika Rosnelly (STMIK Pontianak, 2021)
Learning media at this time are very much needed in the world of education both in schools and lectures, such as macromedia flash applications that are implemented in various types of animation, for example motion animation, sound, video and so on. The research discussed is using motion tweening animation, animation that changes shape and shifts objects. The implemented learning media provides benefits for teachers and students who take part in the training, where there are still many teachers and students who do not understand about making animation using Macromedia Flash. From the results of the training, the benefits of this service activity include improving the skills of teachers and students in being creative in making animations and being able to implement them in schools. The learning method is carried out in students' classrooms using an introduction to animation making tutorial with slides and presentations in front, accompanied by computers related to animation making training materials